REPRESENTASI PESAN ANTI PERUNDUNGAN SOSIAL DALAM FILM "SEPERTI SEHARUSNYA": Analisis Semiotika Roland Barthes - Muhammad Irfan Parama Adi (2024)
REPRESENTATION OF ANTI-SOCIAL BULLYING MESSAGES IN FILM AS IT SHOULD BE (Semiotic Analysis of Roland Barthes) MUHAMMAD IRFAN PARAMA ADI ABSTRACT This research aims to describe and analyze the representation of messages of social bullying for HIV/AIDS sufferers in the film "As Should be." The method used in this research is descriptive qualitative using primary data sources, namely the film "As It Should be," secondary data through literacy and interviews with expert sources. Researchers use scene-by-scene analysis units in their discussion analysis. The research results show that the social bullying experienced by Mr. Reza's family in the film "As It Should" be classified as a type of non-physical bullying, namely intimidation and spreading news that is not necessarily true. Such a film should reflect an anti-social bullying message about not giving up in life's situations whatever the circumstances, never giving up on circumstances. Reflects a picture of an anti-social bullying message about a support system in the environment or providing mutual support for HIV sufferers. Reflects a picture of an anti-social bullying message about prohibiting bullying behavior. Reflects an anti-social bullying message about self-reflection on past mistakes. Reflects an anti-social bullying message about not judging people before knowing the truth. Keywords: HIV/AIDS, Roland Barthes Semiotics, Social Bullying, The Film "As It Should Be"